Systemic association of uveitis in Nepalese population - Shrestha, Jyoti Baba; Shah, Dev Narayan (Journal of Chitwan Medical College, 2017)
Background: Infectious diseases are very common in Nepal and almost all infections are capable of causing uveitis. Parasitic infestations affect large number of Nepalese population and any parasitic infestation can potentially lead to development of uveitis. Local and systemic viral infections, immunological disorder like autoimmune diseases and malignancies can lead  to uveitis. All these emphasize the necessity of proper systemic evaluation and investigation to identify the underlying systemic illness causing uveitis in order to see the pattern of systemic illness and determine the commonest associated systemic disease with uveitis.Methods: A prospective study was conducted at BP Koirala Lions Centre for Ophthalmic Studies from November 2008 to April 2010. All the patients underwent a standard diagnostic protocol when indicated by special tests and procedures performed in order of likelihood.Results: A total of 308 patients with uveitis was seen during the study period. For 146 (47.4%) patients, a specific diagnosis was established based on history, ocular examination and laboratory investigations. A definite association with systemic disease was determined for 82 (26.6%) patients. A well established clinical uveitis entity without a recognizable systemic disorder was present in 64 (20.8%) cases. A diagnosis could not be established in 162 (52.6%) cases. Toxoplasmosis was found to be most frequently associated with uveitis accounting for 5.8 % of the total cases followed by tuberculosis (3.6%), herpes infections (3%), ankylosing spondylitis (2.9%), leprosy (2.3%), sarcoidosis (1.6%) and parasitic infestations (1.3%).Conclusion: The importance of relevant systemic work up in uveitis cases in our set up has been reemphasized by the present study.